The heterogeneity of mesenchymal stem cells: an important issue to be addressed in cell therapy - Jingxuan Li; Zewen Wu; Li Zhao; Yang Liu; Yazhen Su; Xueyan Gong; Fancheng Liu; Liyun Zhang (Stem Cell Research & Therapy, 2023)
Abstract With the continuous improvement of human technology, the medical field has gradually moved from molecular therapy to cellular therapy. As a safe and effective therapeutic tool, cell therapy has successfully created a research boom in the modern medical field. Mesenchymal stem cells (MSCs) are derived from early mesoderm and have high self-renewal and multidirectional differentiation ability, and have become one of the important cores of cell therapy research by virtue of their immunomodulatory and tissue repair capabilities. In recent years, the application of MSCs in various diseases has received widespread attention, but there are still various problems in the treatment of MSCs, among which the heterogeneity of MSCs may be one of the causes of the problem. In this paper, we review the correlation of MSCs heterogeneity to provide a basis for further reduction of MSCs heterogeneity and standardization of MSCs and hope to provide a reference for cell therapy.